Effective Factors Contributing to Acceptance of People With Disability in the Society (Case Study: Shahrekord) - Shahrbanoo Ghafarpoor Nafchi; Asghar Mohammadi (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective The present study tries to examine the effective factors contributing to the acceptance of people with disability in the society. Materials & Methods The study included 4058 disabled persons supported by Welfare Organization of Shahrekord (2474 motional-physical, 673 eyesight, and 911 hearing disability). According to quota sampling method, the statistical sample was 352, which consisted of 58 blind, 80 deaf and 214 motional-physical people with disability. A researcher-made questionnaire was used for gathering the data. Face validity method and Cronbach’s alpha test were used for determining the validity and reliability of the questionnaire. The questionnaire was affirmed by advisor and experienced professor and by using Cronbach’s alpha method for variables of social acceptance of people with disability, social capital, family support, manner of spending leisure, presenting rehabilitation services, transportation facilities, mass media programs, personality characteristics and training, which were found to be 82%, 86%, 94%, 82%, 93%, 85%, 79%, 92% and 87%, respectively. Results Results of Pearson correlation coefficient showed that there was a significant relationship among variables such as social capital, transportation facilities, manner of spending the leisure, presenting rehabilitation services, training and entrepreneur, social media programs, personality characteristics, family support and acceptance of people with disability (P<0.001). There was no relationship between variables such as type (P=0.108), history (P=0.531) and reason of disability (P=0.427) and acceptance of people with disability in the society. According to the results of variance analysis and t-test in terms of demographic characteristics of people with disability, there was no significant difference between gender (P=0.071) and age (P=0.498) and acceptance of people with disability. But, there was a significant difference between education level, occupation of people with disability, and their societal acceptance (P<0.001). People with disability who were highly educated had a higher acceptance in the society. Also, there was a significant difference between marital status (P=0.032) and education level of spouse (P=0.046) and acceptance of people with disability. The most important effective factors on acceptance of people with a disability include social capital (B=0.240), family (B=0.198), type of disability (B=0.164), social media programs (B=0.163), transportation facilities (B=0.159), and entrepreneur and training (B=0.129).  Conclusion Acceptance of people with disability is necessary for their presence in the society and their social relations. We should provide the opportunity for their presence in the society and improve their life through creating proper conditions and possibilities.